ROLE OF THE AMERICAN SOCIETY FOR ENGINEERING EDUCATION IN ENCOURAGING DISTANCE EDUCATION AND OTHER METHODS TO REDUCE COSTS OF ENGINEERING EDUCATION - Walter W. Buchanan (Moscow Polytechnic University, 2022)
During this past year as President of ASEE, I worked to lead our society in playing a role in encouraging distance education and other methods to reduce the cost of engineering education. In the United States and other countries as well, the cost of higher education has been increasing. This past year student debt surpassed the total of credit card debt in the United States to the tune of over one trillion dollars. This milestone has generated a lot of attention and forced many people to see what can be done to decrease the cost of higher education. Engineering education tends to be higher than education in many other disciplines due to the cost of running and equipping laboratories, which are very important in good hands-on engineering education. Distance education can play a role here. "Flipped" classrooms where lectures can be done by distance education followed by live discussions and laboratories is one example of what can be done to reduce costs. Other methods will be discussed.